The Meaning of the Word “Wazir” in the Qur’an: A Semantic Analysis - Nur Rochim, Mohammad Rizal; Nugroho, Kharis; Nirwana, Andri (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
The purpose of this study is to explore and understand the meaning of the word "wazir" in the Quran. This study employs a library research method, which requires the researcher to conduct a thorough examination of various textual sources and literature related to the word. The approach used in this research is Toshihiko Izutsu's Quranic semantic approach. The research findings indicate that the meaning of the word "wazir" in the Quran is complex, with strong connotations related to the concepts of sin and heavy or significant accountability. Understanding the word "wazir" is crucial, as it not only reflects linguistic understanding but also has profound moral and ethical implications in Islam. Semantic analysis of the word "wazir" provides insights for a deeper understanding of the moral and ethical values embedded in the Quran, as well as how this vocabulary reflects and portrays the fundamental principles of the religion in the sacred text.